2017
DOI: 10.20473/j.djmkg.v50.i4.p178-182
|View full text |Cite
|
Sign up to set email alerts
|

Composite resin shear bond strength on bleached dentin increased by 35% sodium ascorbate application

Abstract: Background: Restoration of the teeth immediately after bleaching with 35% hydrogen peroxide (H 2 O 2 ) is contraindicated due to the remnant of free radicals that will stay inside enamel and dentin for 1-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…11 Similarly, Nugraheni et al revealed that two applications of 35% sodium ascorbate could increase the strength of composite resin shear in teeth after bleaching with 35% H 2 O 2 . 12 Coppla et al also demonstrated that double application of 35% sodium ascorbate in 5-10 minute intervals could restore the bonding strength of post-bleaching enamel as well as non-bleached enamel. 7 Sodium ascorbate is a derivative of ascorbic acid which is widely used as an antioxidant, but has unstable properties, and thus to achieve effective results it is necessary to add substances that can increase the stability of sodium ascorbate, including stabilizers or preservatives, such as citric acid, boric acid or tartaric acid, synergists, and emulsifiers such as surfactants.…”
Section: Introductionmentioning
confidence: 97%
“…11 Similarly, Nugraheni et al revealed that two applications of 35% sodium ascorbate could increase the strength of composite resin shear in teeth after bleaching with 35% H 2 O 2 . 12 Coppla et al also demonstrated that double application of 35% sodium ascorbate in 5-10 minute intervals could restore the bonding strength of post-bleaching enamel as well as non-bleached enamel. 7 Sodium ascorbate is a derivative of ascorbic acid which is widely used as an antioxidant, but has unstable properties, and thus to achieve effective results it is necessary to add substances that can increase the stability of sodium ascorbate, including stabilizers or preservatives, such as citric acid, boric acid or tartaric acid, synergists, and emulsifiers such as surfactants.…”
Section: Introductionmentioning
confidence: 97%
“…So, the termination process occurs earlier in the formation of polymer chains. 4 The inhibition of the resin tag penetration and polymerization process can reduce physical properties such as the bond strength of adhesive material to dentin, and increase the microleakage of composite resin restorations. 4 Previous studies have stated that naturally, free radicals in the dentinal tubules take one to three weeks to disappear.…”
Section: Introductionmentioning
confidence: 99%
“…4 The inhibition of the resin tag penetration and polymerization process can reduce physical properties such as the bond strength of adhesive material to dentin, and increase the microleakage of composite resin restorations. 4 Previous studies have stated that naturally, free radicals in the dentinal tubules take one to three weeks to disappear. 5 However, delayed restoration can lead to a higher risk of crown fracture and loss of temporary restorations, leading to re-discoloration.…”
Section: Introductionmentioning
confidence: 99%
“…In this research the magnitude of force acceptable for composite resin restorations was measured when the restorations were detached from the tooth surface. Shear strength can indicate how the adhesion occurs in vitro 16 .…”
Section: Introductionmentioning
confidence: 99%